Acute Myeloid Leukemia Presenting as Galactorrhea. Issue 4 (1st October 2016) - Nambiar, K. Rakul; Nair, Sreejith G.; Devi, R. Nandini
Abstract : Acute myeloid leukemia (AML) presents with symptoms related to pancytopenia (weakness, infections, bleeding diathesis) and organ infiltration with leukemic cells. Galactorrhea is an uncommon manifestation of AML. We report a case of AML presenting with galactorrhea.